1963
DOI: 10.1126/science.142.3600.1657
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Changes in the Liver Endoplasmic Reticulum: Association with Drug-Metabolizing Enzymes

Abstract: The cellular changes which lead to the increase of drug-metabolizing enzymes following drug administration are explained by correlating new biochemical data with previously reported electron microscopic and pharmacologic observations. Repeated administration of phenobarbital and several other drugs results in a quantitative increase of the smooth endoplasmic reticulum of the liver cell. The marked increase in drug-metabolizing enzymes is found to occur in this enlarged smooth membrane fraction of the endoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
0
1

Year Published

1967
1967
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 384 publications
(87 citation statements)
references
References 8 publications
11
75
0
1
Order By: Relevance
“…Thus, it seems that the decrease in ALT and AST activities enhanced the induction of microsomal drug-metabolizing enzymes, and these regulatory controls may act to conserve nutrients and energy for the cells. These results are in consonance with the studies of Orrhenuis et al (1965), Marshall (1978, Remmer and Merker (1993), and Singh et al (1998). The reports of these workers showed that increased protein synthesis due to increased glucuronidation of the endoplasmic reticulum and decreased permeability of the liver cells resulted in induction of the microsomal drugmetabolizing enzymes.…”
Section: Discussionsupporting
confidence: 82%
“…Thus, it seems that the decrease in ALT and AST activities enhanced the induction of microsomal drug-metabolizing enzymes, and these regulatory controls may act to conserve nutrients and energy for the cells. These results are in consonance with the studies of Orrhenuis et al (1965), Marshall (1978, Remmer and Merker (1993), and Singh et al (1998). The reports of these workers showed that increased protein synthesis due to increased glucuronidation of the endoplasmic reticulum and decreased permeability of the liver cells resulted in induction of the microsomal drugmetabolizing enzymes.…”
Section: Discussionsupporting
confidence: 82%
“…Differential induction of microsomal CYP activities by aryl hydrocarbons and phenobarbital was discovered over 50 years ago [1][2][3][4], and facilitated characterization of the CYP supergene family [5,6]. This discovery also stimulated identification of the responsible ligand-activated transcription factors (LATFs): AhR [7,8], CAR and PXR [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present commentary emphasizes regulation of human hepatic UGTs by LATFs and their multilevel crosstalk. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The administration of phenobarbital markedly increases the activities of drug-oxidiz ing, drug-reducing enzymes and NADPH-dependent electron transport enzymes and the amounts of cytochrome b5 and P-450 (2,4,5,15,16,32,33,36,37). Since the effect of phenobarbital is likely due to an increased synthesis of the microsomal enzymes (2, 38 42), the effect of phenobarbital on the activities of drug-metabolizing enzymes and NADPH dependent electron transport system was investigated.…”
Section: Fig 1 Activities Of Pentobarbital Oxidase Carisoprodol Oxmentioning
confidence: 99%